Perbaikan Proses Produksi Minuman Markisa di Bantar Gebang: Indonesia - Lutfi Alhazami (JPM: Jurnal Pengabdian Masyarakat, 2022)
Passion fruit is a fruit that can grow in tropical climates like Brazil. Indonesia also has the same climate so that passion fruit in Indonesia can also grow. Passion fruit does not have a long storage time because of its high water content. Therefore, passion fruit juice is an alternative that can be consumed longer. With a fairly high water content, there is a need for special handling that needs to be taught to the public to increase the durability of passion fruit syrup products. Various methods such as adding additives have also been carried out, but the results can affect fruit juice. Therefore, in this community service, the passion fruit drink was preserved by heat treatment using a heater and a cooker. This activity was carried out with the Bantar Gebang community at the Tunas Mulya Natural School. The result of this activity was that previously the production and preservation process for passion fruit drinks could only last up to 3 days, but with a different process and cooking utensils, the drinks can last up to 7 days outside the refrigerator